Hydrology in Practice. - Beven, Keith J.; Chappell, Nick A.; Lamb, R. (Rob) (Taylor & Francis, 2010)
Hydrology in Practice is an excellent and very successful introductory text for engineering hydrology students who go on to be practitioners in consultancies, the Environment Agency and elsewhere. It has never been superseded by any other text in this respect. This fourth edition of Hyrodology in Practice while retaining all that is excellent about its predecessor, by Elizabeth Shaw, replaces the material on the Flood Studies Report with an equivalent section on the methods of the Flood Estimation Handbook and its revisions. Other completely revised sections on instrumentation and modelling reflect the many changes that have occurred over recent years. The updated text has taken advantage of the extensive practical experience of the staff of JBA Consulting who use the methods described on a day-to-day basis. Topical case studies further enhance the text and the way in which students at undergraduate and MSc level can relate to it. The fourth edition will also have a wider appeal outside the UK by including new material on hydrological processes which also relate to courses in geography and environmental science departments. In this respect the book draws on the expertise of Keith Beven and Nick Chappell who have extensive experience of field hydrological studies in a variety of different environments, and teaching undergraduate hydrology courses for many years. Second and final year undergraduates (and MSc) students of hydrology in Engineering, Environmental Science and Geography Departments across the globe, as well as professionals in environmental protection agencies and consultancies, will find this book invaluable. It is likely to be the course text for every undergraduate/MSc hydrology course in the UK and in many cases overseas too.